2018
DOI: 10.1371/journal.pone.0202169
|View full text |Cite
|
Sign up to set email alerts
|

Considering parental hearing status as a social determinant of deaf population health: Insights from experiences of the "dinner table syndrome"

Abstract: The influence of early language and communication experiences on lifelong health outcomes is receiving increased public health attention. Most deaf children have non-signing hearing parents, and are at risk for not experiencing fully accessible language environments, a possible factor underlying known deaf population health disparities. Childhood indirect family communication–such as spontaneous conversations and listening in the routine family environment (e.g. family meals, recreation, car rides)–is an impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…One 2013 survey included a question concerning retrospective perception of adults who were DHH of how well they understood family conversations. 18 In a sample of 211 adults who answered this question, 81% (141 of 175) of respondents who had hearing parents and 18% (4 of 22) of respondents who had parents who were DHH reported lower levels of understanding indirect family conversations. Even when direct communication access is not obstructed (e.g., if parents sign adequately to a signing child who is DHH), missing out on incidental family conversations can occur when a child who is DHH has trouble understanding conversations that caregivers have with other family members.…”
mentioning
confidence: 99%
“…One 2013 survey included a question concerning retrospective perception of adults who were DHH of how well they understood family conversations. 18 In a sample of 211 adults who answered this question, 81% (141 of 175) of respondents who had hearing parents and 18% (4 of 22) of respondents who had parents who were DHH reported lower levels of understanding indirect family conversations. Even when direct communication access is not obstructed (e.g., if parents sign adequately to a signing child who is DHH), missing out on incidental family conversations can occur when a child who is DHH has trouble understanding conversations that caregivers have with other family members.…”
mentioning
confidence: 99%
“…Research with D/HH persons found that social participation and feeling included in group conversations as well as being recognized and accepted as a deaf member in their environment were related to QoL (Kushalnagar et al, ). Research has also shown that having a deaf parent is associated with benefit to a deaf child (Hall, Smith, Sutter, DeWindt & Dye, ; Yoshinaga‐Itano, Sedey, Wiggin & Chung, ). Deaf mentor programs provide an alternative way to connect a family, comprised of hearing parents with a D/HH child, with a D/HH adult role model.…”
Section: Discussionmentioning
confidence: 99%
“…40 A small number of studies have investigated pragmatic skills of DHH adolescents when conversing with more or less familiar peers and adults. The findings of these studies 33,43,44 suggest that although conversations between DHH adolescents and peers or adults are marked by unrepaired misunderstandings, communication appears more effective when interacting with someone familiar (eg, a parent or friend). This hypothesis is supported by Ibertsson et al, 39 who found that pairs of hearing and deaf teenagers with CIs engaged in productive conversations when they knew one another well, suggesting that joint communication skills in mixed DHH-hearing pairs can be developed over time.…”
Section: Adolescencementioning
confidence: 94%
“…More than 80% of deaf adults who have hearing parents report being left out of conversations with their hearing family members most of the time. 43…”
Section: Adolescencementioning
confidence: 99%